INSTITUTIONAL DIMENSION OF SUSTAINABLE DEVELOPMENT - Pivašević, Jelena M; Hafner, Petar (International Journal of Economic Practice and Policy, 2014)
Sustainable development is a complex, multidimensional concept, which is becoming increasingly important in the modern business environment and one of the main topics of scientific debate. Sustainable development is based on three interrelated pillarsthat is, the economic, social and environmental. However, the new research trends identified some additional dimensions of sustainable development, as well as cultural and institutional dimensions. This paper discusses the institutional aspects of sustainable development, as a necessary element, which should connect and support other dimensions of sustainable development. The aim of this paper is to show the importance of having the appropriate institutional apparatus for the implementation of sustainable development policy